The Foundations of Fiction. - Master Teaching Assistant, Writing; Rendell, Joanne; Brody, Jessica (linkedin.com, 2019)
Learn how to write compelling novels, memoirs, short stories, or screenplays. Explore the fundamentals of great fiction and get practical tips to you sharpen your own writing.